The Effectiveness of Unconventional Monetary Policy (UMP) on Financial Markets in Indonesia and Malaysia during the Covid-19 Pandemic - Ardina Yulia Putri; Sugiharso Safuan (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
Abstract: This paper discusses the effectiveness of unconventional monetary policy (UMP) on financial markets, includes the exchange rate and stock return index in Indonesia and Malaysia during the Covid-19 pandemic. Using announcements issued by the central banks of Indonesia and Malaysia as a benchmark for changes of yield curve in response to UMP, the effectiveness of UMP on exchange rates and stock return index is estimated using the sign and zero restriction VAR. As a result, UMP is effective on exchange rates in Indonesia and Malaysia, but it is not effective on stock return index in those two countries.